2020
DOI: 10.1029/2020gl090243
|View full text |Cite
|
Sign up to set email alerts
|

The Dimmest State of the Sun

Abstract: How the solar electromagnetic energy entering the Earth's atmosphere varied since preindustrial times is an important consideration in the climate change debate. Detrimental to this debate, estimates of the change in total solar irradiance (TSI) since the Maunder minimum, an extended period of weak solar activity preceding the industrial revolution, differ markedly, ranging from a drop of 0.75 W m −2 to a rise of 6.3 W m −2. Consequently, the exact contribution by solar forcing to the rise in global temperatur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…The higher level of the magnetic flux during periods of very low solar activity (e.g., during the Maunder and the Dalton minima, see Fig. 4) will presumably lead to a weaker secular variation in the total solar irradiance (TSI) and in particular the rise in the TSI since the Maunder minimum (cf., Yeo et al 2020), an important parameter for understanding the influence of solar irradiance variability on long-term climate A70, page 7 of 8 trends (e.g., Gray et al 2010;Solanki et al 2013). The influence of the revised magnetic flux time series on TSI will be the subject of a future investigation.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The higher level of the magnetic flux during periods of very low solar activity (e.g., during the Maunder and the Dalton minima, see Fig. 4) will presumably lead to a weaker secular variation in the total solar irradiance (TSI) and in particular the rise in the TSI since the Maunder minimum (cf., Yeo et al 2020), an important parameter for understanding the influence of solar irradiance variability on long-term climate A70, page 7 of 8 trends (e.g., Gray et al 2010;Solanki et al 2013). The influence of the revised magnetic flux time series on TSI will be the subject of a future investigation.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In principle, these reconstructions have no lower limit for the TSI corresponding to minimal magnetic activity. However, in practice, because based on today's observational resolution, it is found that the magnetic content of the quiet Sun is found to be not much larger than about the amplitude to the maximum, the lowest limit to the dimmest state of the Sun has been derived to be about 2 W/m 2 below the 2019 minimum (Yeo et al, 2020). Thus, the reduction of a 31-year average TSI during the Maunder minimum relative to today's TSI would be about 2.5 W/m 2 .…”
Section: Indirect Solar Forcingmentioning
confidence: 99%
“…Recently, the MURaM simulations accounting for the effect of a small-scale dynamo became available (see, e.g., Rempel, 2018Rempel, , 2020, and the references therein). Utilising these simulations, Yeo et al (2020) found that the change of the TSI between 2019 and Maunder minimum could not be larger than 2 ± 0.7 W m −2 .…”
Section: A New Generation: Physics-based Irradiance Modelsmentioning
confidence: 99%
“…An improved understanding of the interactions between magnetic fields and matter in stellar atmospheres brought about by MHD simulations constitutes another important area of progress in modeling solar and stellar brightness variations. The MHD simulations of the solar atmosphere have already been used for reconstructing TSI variability and for constraining its secular component (Rempel, 2020;Yeo et al, 2020). In the absence of any direct observations of stellar magnetic features, there have been a number of attempts to modify solar semi-empirical models and apply them for modeling brightness variations of solar-like stars (see, e.g., Witzke et al, 2018Witzke et al, , 2020.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
See 1 more Smart Citation